2022
DOI: 10.1111/1750-3841.16098
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of α‐amylase and α‐glucosidase by Morus australis fruit extract and its components iminosugar, anthocyanin, and glucose

Abstract: The inhibition of α‐amylase and α‐glucosidase are important for the maintenance of blood glucose level. Mammalian α‐glucosidase includes maltase–glucoamylase and sucrase–isomaltase complexes. In this study, we examined the inhibitory effects of Morus australis fruit extract and its components, that is, three iminosugars (1‐deoxynojirimycin [1‐DNJ], fagomine, and 2‐O‐α‐D‐galactopyranosyl deoxynojirimycin), two anthocyanins (cyanidin‐3‐glucoside and cyanidin‐3‐rutinoside), and glucose, against α‐amylase and α‐gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 31 publications
1
4
0
Order By: Relevance
“…First, the presence of maltose in feces indicates that maltose production occurred, but further degradation did not occur, indicating that the inhibition of α-glucosidase, mainly DNJ-1, by MLP was stronger than the inhibition of α-amylase activity. This result is consistent with previous findings showing that 1-DNJ also has inhibitory activity against α-amylase, but is less potent than its inhibitory activity against α-glycosidase [ 42 , 43 , 44 ]. Furthermore, it is likely that maltose, which may have been produced in the upper gastrointestinal tract and small intestine, was not efficiently degraded or utilized by bacteria in the colon and was excreted in the feces.…”
Section: Discussionsupporting
confidence: 93%
“…First, the presence of maltose in feces indicates that maltose production occurred, but further degradation did not occur, indicating that the inhibition of α-glucosidase, mainly DNJ-1, by MLP was stronger than the inhibition of α-amylase activity. This result is consistent with previous findings showing that 1-DNJ also has inhibitory activity against α-amylase, but is less potent than its inhibitory activity against α-glycosidase [ 42 , 43 , 44 ]. Furthermore, it is likely that maltose, which may have been produced in the upper gastrointestinal tract and small intestine, was not efficiently degraded or utilized by bacteria in the colon and was excreted in the feces.…”
Section: Discussionsupporting
confidence: 93%
“…The glucose concentration in the M. australis dried fruit was 123-262 mg/g [13]. We also reported that 1-DNJ and glucose are the components in M. australis fruit, that are involved in the inhibition of maltase, glucoamylase, sucrase, and isomaltase [13].…”
Section: Introductionmentioning
confidence: 79%
“…We previously reported that the 1-DNJ concentration in the M. australis dried fruit were 0.04-0.29 mg/g, which was considerably smaller than that in the M. australis leaf (4.0 mg/g) [11,13]. The glucose concentration in the M. australis dried fruit was 123-262 mg/g [13]. We also reported that 1-DNJ and glucose are the components in M. australis fruit, that are involved in the inhibition of maltase, glucoamylase, sucrase, and isomaltase [13].…”
Section: Introductionmentioning
confidence: 83%
See 2 more Smart Citations